Stand-up Comedy as Contemporary Live Theatre - Idowu James Adekunle (Journal of Humanistic and Social Studies, 2020)
Stand-up comedy is a new subgenre of comedy that widely watches across the globe. It is a form of aesthetic performance that elicits laughter and also brings succour and mirth to its audience. Its therapeutic mode, although temporal, gives a thorough and sound approach to life’s issues in a mild way. Stand-up comedy show has been proven to be one of the major components of pleasurable shows. However, many scholars viewed stand-up comedy as mere entertainment and humorous show without taking a deeper look at its theatrical performance. Therefore, this paper examines stand-up comedy as a contemporary live theatre. Besides, it investigates the dialoguing conversational techniques of characters, paralinguistic features of the stage play and the use of music, symbolism, caricature, subtle irony, humour, blazer costume, improvisation and interactivity in a bid to show stand-comedy as a contemporary live theatre. Schechner’s Performance, Freudian and Jungian psychoanalytic theories were used to analyse the aesthetic unique performances of the stand-up comedians. The purposively selected stand-up comedian for stage show is Klint De Drunk (Ahamefula Igwemba) and supported by Basket Mouth (Bright Okpocha). Live digital discs of performance recordings of Klint De Drunk were used. Data were subjected to performance and literary analyses.